2009
DOI: 10.1111/j.1469-0691.2008.02663.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility among Staphylococcus epidermidis isolated from prosthetic joint infections with special focus on rifampicin and variability of the rpoB gene

Abstract: Staphylococcus epidermidis is the most important pathogen in infections related to implanted foreign materials, especially prosthetic joint infections (PJIs). The aim of this study was to investigate the antimicrobial activities of 16 antibiotics against S. epidermidis isolated from PJIs, with special focus on rifampicin and rpoB variability. Ninety-one per cent of the isolates were multiresistant (i.e. resistant to members of more than three classes of antibiotics). Thirty-nine per cent were resistant to rifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
42
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 39 publications
11
42
4
2
Order By: Relevance
“…The prevalence of erythromycin-resistant strains was significantly lower in other studies (30)(31)(32). On the other hand, we found that 10 biofilm and non-biofilm-producing strains showed susceptibility to all tested antibiotics except for penicillin; these findings are consistent with our previous reports for S. aureus strains (17,(33)(34)(35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of erythromycin-resistant strains was significantly lower in other studies (30)(31)(32). On the other hand, we found that 10 biofilm and non-biofilm-producing strains showed susceptibility to all tested antibiotics except for penicillin; these findings are consistent with our previous reports for S. aureus strains (17,(33)(34)(35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 83%
“…Rifampin, which is probably the single most important drug currently used against biofilm infections of arthroplasties (49), was not investigated in the present study because of the existence of many experimental and clinical data (50). Although rifampin is very active against bacterial and staphylococcal biofilms in particular, resistance to rifampin is increasing in many organisms and not only staphylococci (22,28). The question is how heat can be applied topically and used for a long period without risking thermal burns.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Rifampicin is considered to be the antimicrobial agent of choice for the treatment of CIED, since previous studies have shown that, in combination with other antimicrobials (usually linezolid or teicoplanin), rifampicin is able to prevent vascular infections caused by methicillin-resistant S. aureus and S. epidermidis. (11,13,18) Still using rifampicin, the AIGIS (RX)® product was developed to provide a novel approach by creating an antibiotic mesh in which a variety of devices can be implanted to reduce the development of infections in cardiac implants. This product combines rifampicin and minocycline and has been effective in preventing cardiac device colonization and clinical infections by S. aureus.…”
Section: Discussionmentioning
confidence: 99%